Effects of different levels of soil moisture and indigenous organic amendments on the yield of boro rice grown under field condition (Dhaka University Journal of Biological Sciences, 2020)
A field study was conducted to determine the potentials of moist (70% soil moisture) and saturated (> 100% soil moisture) soil conditions and organic amendments of rice straw compost (RSC), mustard meal (MM) and trichocompost (TC) on the selected rice varieties of BR 3, local BRRI dhan 29 and BRRI dhan 74 in relation to the growth and yield attributes of rice varieties. The rates of amendments were 0, 4, 8 t/ha for RSC; 0, 3, 6 t/ha for MM and 0, 2.5, 5 t/ha for TC. The maximum grain yield of 8.71 t/ha was attained from the RSC4ML100 and 8.58 t/ha from RSC4ML70 treatments. The moist condition of soil had almost similar effects on the number of productive tillers, grain yield, number of filled and fissured grains, 1000-grain weight and harvest index as compared to saturated condition along with the doses of RSC, MM and TC. The RSC (4 t/ha) was the superior treatment with respect to the growth and yield components of rice followed by the treatments of TC (2.5 t/ha) and MM (3 t/ha), irrespective of rice varieties and moisture levels.Dhaka Univ. J. Biol. Sci. 29(1): 87-96, 2020 (January)